The study of the biological age of university teachers in the period of urgent transition to distance education as a result of pandemic - Myrzabayev, A.B.; Tnimova, G.T.; Sokolova, G.G.; Bodeyev, M.T.; Kabdolla Е. (Fundamental and Experimental Biology, 2023)
In the article, the biological age of university teachers was studied (using the express method of V.P. Voytenko), a total of 127 people (64 women, 63 men) were examined, they were divided into three groups according to their age (1st group ‒23-39 years old, 2nd group ‒40-59 years old, 3rd group ‒60 years old and older).A special health self-assessment questionnaire and a number of physiological indicators and mathematical formulas were used to calculate the value of biological age (BA);the appropriate biological age value (ABA) was calculated; he obtained biological age and the corresponding biological age were compared, it was determined how many years the subjects’ aging rate was ahead or behind their peers. This approach makes it possible to divide people of the same age into several degrees according to the degree of “age wear”, as well as according to the “reserve” of health (degrees I and II ‒slow aging, III ‒BA corresponds to the population standard, IV and V ‒accelerated aging). The research was conducted during the transition of universities to distance education during the pandemic (October-November, 2020). More than half of the teachers (55.90%) were found to be experiencing accelerated aging (grade IV-V of BA), and this was more common among men than among women. Among those examined, the rate of aging is evident in the youngest group of teachers. Due to the pandemic, in the period of urgent transition from the usual traditional educational format to distance learning, the accelerated rate of aging according to biological age indicators was observed in almost all groups of teachers: 23%-80%. And there is a conclusion that the gender and age of the subjects affect the biological age.